THE INTENSITY WATCHING TELEVISION TO COMMUNICATION OF PARENTS AND SCHOOLD-AGE CHILDREN (studied in the village of Padas district of Dagangan Madiun regency) - Edy Purnomo; . Muarrofah; Agustina Maunaturrohmah (Jurnal Keperawatan, 2012)
Television is a media that most attract attention and electronic goods purchased by many people among other mass media. In today's world of mass media, busied cases of children with media especially watching television, being led to the "crisis of the parents" which greatly affects the communication between parents and children. The purpose of this research was to determine the effect intensity of watching television to the communication of parent and school-age children in the village of Padas district of Dagangan Madiun regency.This research design was analytic cross sectional. The population was all parents who had school-age children in the village of Padas district of Dagangan Madiun regency in 2012 amounted to 75 people. The sampling technique used proportional random sampling with the sample a number of 43 people. The independent variable was the intensity of watching television and the dependent variable was the communication of parent and school-age children. The research instrument used a questionnaire with data processing by editing, coding, scoring, tabulating and statistic test used chi square. The result of intensity watching television was majority passive amounted 22 respondents (51,2%). Most of communication of parents and school-age children was good with total 21 respondents (48,8%). From the result of cross tabulation known that respondents children who’s watching television with passive intensity were 21 respondents (48,8%) the communiction between parents and children was good. Statistic test of chi square showed that the value of p = 0,000 which less than alpha (0,05), so H0 rejected H1 accepted. This research can be concluded that there is effect on intensity watching television to the communication of parents and school-age children in the village of Padas district of Dagangan Madiun regency.